Analisis Hukum Tanggung Jawab Scribd Terhadap Unggahan Dokumen Informasi Akses Virtual Private Network (Vpn) - Pratistita, Made Wipra (Fakultas Hukum Universitas Primagraha, 2024)
Activities in exchanging information and sharing knowledge through internet network-based facilities are one part of Digital Literacy. However, these information exchange activities are sometimes vulnerable to leakage of confidential information. One of them is related to the case of uploading state documents containing confidential information on the SCRIBD website. In this article written using normative legal research methodology, primary legal sources from legislation regarding the operation of electronic systems and secondary legal materials in the form of books and articles on informatics law are used. The resulting conclusion is that regulations in Indonesia need to be updated in an effort to hold electronic system operators legally accountable for uploading documents that are prohibited by statutory regulations.